Shape-Controlled Self-Assembly of Light-Powered Microrobots into Ordered Microchains for Cells Transport and Water Remediation - Peng, Xia; Urso, Mario; Ussia, Martina; Pumera, Martin (ACS nano, 2022)
Nature presents the collective behavior of living organisms aiming to accomplish complex tasks, inspiring the development of cooperative micro/nanorobots. Herein, the spontaneous assembly of hematite-based microrobots with different shapes is presented. Autonomous motile light-driven hematite/Pt microrobots with cubic and walnut-like shapes are prepared by hydrothermal synthesis, followed by the deposition of a Pt layer to design Janus structures. Both microrobots show a fuel-free motion ability under light irradiation. Because of the asymmetric orientation of the magnetic dipole moment in the crystal, cubic hematite/Pt microrobots can self-assemble into ordered microchains, contrary to the random aggregation observed for walnut-like microrobots. The microchains exhibit different synchronized motions under light irradiation depending on the mutual orientation of the individual microrobots during the assembly, which allows them to accomplish multiple tasks, including capturing, picking up, and transporting microscale objects, such as yeast cells and suspended matter in water extracted from personal care products, as well as degrading polymeric materials. Such light-powered self-assembled microchains demonstrate an innovative cooperative behavior for small-scale multitasking artificial robotic systems, holding great potential toward cargo capture, transport, and delivery, and wastewater remediation.
Keywords: micromotors; photo-Fenton degradation; swarming; polymery; magnetismus; Water; Polymers; collective behavior; self-assembly; cargo transport; Magnetics; voda